2018
DOI: 10.1038/s41598-018-31030-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of the HOXD8 transcription factor in cisplatin resistance and tumour metastasis in advanced epithelial ovarian cancer

Abstract: Few studies have examined the potential transcription factor (TF) simultaneously associated with cisplatin resistance and metastasis in ovarian cancer. To assess a related mechanism, a 345-channel protein/DNA array and transcriptional activity ELISA were performed to compare the TF activities in the cisplatin-sensitive SKOV3 and cisplatin-resistant SKOV3-DDP cells and in HO-8910 and the homologous highly metastatic HO-8910PM cells. In SKOV3-DDP vs. SKOV3 cells, 43 TFs were up-regulated, while 31 were down-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In our work, we proved that serum exosomal miR-744 is downregulated in HCC tissues. In addition, we identified that a direct target of miR-744 is PAX2, which has been indicated to regulate the chemotherapy response in several cancers [3234]. In HCC, PAX2 is in high expression level in cancer tissues compared with adjacent normal tissues, which is contrary to the expression of miR-744.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we proved that serum exosomal miR-744 is downregulated in HCC tissues. In addition, we identified that a direct target of miR-744 is PAX2, which has been indicated to regulate the chemotherapy response in several cancers [3234]. In HCC, PAX2 is in high expression level in cancer tissues compared with adjacent normal tissues, which is contrary to the expression of miR-744.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin has been the chemotherapy of choice against OC for a long time 14 and the development of resistance against cisplatin remains a major clinical hindrance in the effective therapy of OC patients 15 . Role of several factors 16 , 17 , including epigenetic factors 18 has been pursued in the acquired cisplatin resistance in OC. Additionally, in recent years, a number of lncRNAs have been proposed/investigated for their possible role in cisplatin sensitivity and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…These are CDKN2A [11,23], RB1 [10,11] ], PIK3CA [12], AKT3, HOXD8 [12], PAX5 [23], MAP3K8 [24], and MITF [12]. All these genes are either involved in the regulation of the aforementioned MAPK and PI3K/AKT signaling pathways or they are tumor suppressors affecting drug resistance in other cancers (HOXD8, [25]; PAX5, [26]). The panel of selected genes and variants is of course not exhaustive and there are other putative genetic biomarkers of melanoma resistance to be discovered.…”
Section: Introductionmentioning
confidence: 99%